GIS BASED SPATIAL MAPPING OF SOIL NUTRIENT STATUS OF PAUNI BLOCK OF MAHARASHTRA, INDIA - SUMEDH R. KASHIWAR; M. C. KUNDU; USHA R. DONGARWAR (The Bioscan, 2021)
A study was conducted with an aim to assess the soil fertility status along with geospatial mapping of available nutrients in the soils of Pauni block of Maharashtra, India during the year 2015 to 2018. The 134 composite georeferenced surface soil samples were collected from entire study area and thereafter analyzed with standard methodology. The results revelated that, 101 (75.4%) samples were neutral in soil reaction and organic carbon was found low in 66 (49.3%) and medium in 67 (50%) soil samples. In terms of nitrogen, 84.3% samples were found medium (280-560 kg ha -1 ), whereas, both phosphorus and potassium contents were found high in major area. Sulphur content was also low in 61.9% soil samples. The micronutrients like zinc, iron and boron were deficient in 61.9% (87 samples), 59% (79 samples) and 100% of soil samples respectively. Only copper and manganese contents were found high in 85.8% and 81.3% soil samples respectively. The available N, K, P, S, Zn, Fe, Cu, Mn and B contents were categorized as marginal, very high, very high, low, low, low, very high, very high and very low respectively using nutrient index values (NIV). Defienct soil nutrient should be replenished by adding fertilizers and manures for enhancing soil fertility and crop productivity.